EFEKTIVITAS PENGGUNAAN BAHASA PEMROGRAMAN PHP LARAVEL DENGAN PHP NATIVE PADA PENGEMBANGAN WEBSITE - andayaningtyas, novi (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2024)
To design a website, many web developers use the PHP programming language. Currently, the concept that is widely used in application development is the object-oriented programming or OOP approach. However, designing such a website is still considered lengthy and incurs a significant cost when done from scratch. Therefore, an effective and efficient solution for designing a website is to use a PHP framework. The aim of this research is to analyze the comparison between websites that implement the Laravel framework and websites that implement native PHP based on lines of code, code efficiency, speed, folder structure and URL, architecture, and web security. Each website is built using a MySQL database system, PHP7 as the native language, Laravel as the PHP framework, and Apache as the web server.